EMPLOYMENT DISCRIMINATION AGAINST SMOKERS (Tufts Archival Research Center, 2007)
Confidential; Memorandum to the Tobacco Institute files regarding employment discrimination against smokers. Reviews ways to challenge hiring discrimination against smokers as violations of federal law. Accepts that neither common law nor constitutional provisions protect smokers from employment discrimination. Examines civil rights laws as well as other labor laws. Uses past cases as support for anti-discrimination arguments.